Strategi Komunikasi Pemasaran Perusahaan Gas Negara Area Karawang Dalam Meningkatkan Pelayanan Pada Pelanggan - Sal Shadila Nurfaddilah; Ana Fitriana Poerana; Luluatu Nayiroh (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is motivated by a surge in customer visits at the customer service facility of Perusahaan Gas Negara Karawang Area due to the lack of information received by customers. This happened because of the delegation of customer management from the Ministry of Energy and Mineral Resources to PGN Karawang Area. Therefore, PGN Karawang Area plans and implements a marketing communication strategy that can reduce and stabilize the volume of customer visits. This study aims to determine the marketing communication strategies that are implemented to achieve success in reducing the volume of customer visits. The research method used is a qualitative research method with a case study approach. The theory used is the theory of Integrated Marketing Communication (IMC). The data collection method used participant observation by conducting in-depth interviews and documentation. The results obtained indicate that the strategy that has been implemented by PGN Area Karawang has succeeded in reducing and stabilizing the volume of customer visits because customers have received sufficient information, made it easier to get service, and received satisfactory service.